2013
DOI: 10.1111/j.1756-1051.2013.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Dust seed production and dispersal in Swedish Pyroleae species

Abstract: Dust seeds are the smallest seeds in angiosperms weighing just about a few micrograms. Th ese seeds are characteristic of most orchids, and several studies have been performed on seed features, fecundity and dispersal of orchid dust seeds. In this study we examine seed features, seed production and seed dispersal in another plant group with dust seeds, the Pyroleae (Monotropoideae, Ericaceae), focusing on six species: Pyrola chlorantha , P. minor , P. rotundifolia , Chimaphila umbellata , Moneses unifl ora and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Seed production per capsule is on average 7800 in C. umbellata , 7000 in Moneses uniflora and 2500–3000 in the two Pyrola species (Johansson et al . ). Seed production in M. hypopitys has, to our knowledge, not been investigated.…”
Section: Methodsmentioning
confidence: 97%
“…Seed production per capsule is on average 7800 in C. umbellata , 7000 in Moneses uniflora and 2500–3000 in the two Pyrola species (Johansson et al . ). Seed production in M. hypopitys has, to our knowledge, not been investigated.…”
Section: Methodsmentioning
confidence: 97%
“…Machon et al [47] found that 95% of Spiranthes spiralis seeds were trapped less than 1.35 m from infructescences, and 50% were noted within 5 cm of the nearest fruiting plants. In other plants with dust seeds, for example from the genus Pyrola, the vast majority of seeds are deposited close to the seed source [42]. Short-distance dispersal of orchid seeds is also suggested in studies presenting and interpreting results of population genetic variation [12,13,27,54].…”
Section: Factors Influencing Seed Dispersal In Orchidsmentioning
confidence: 99%
“…40 km) by air and to be among the first plants to colonize the island after the 1883 eruption. Besides seed properties, vegetation type, wind characteristics, and plant size are the most often considered factors influencing dispersal distance in species with dust seeds [16,[40][41][42]. Although some authors have stated that information about long-distance dispersal over more than 10-15 km should be regarded as extremely rare [43], it is often reported in orchid literature [28,33,38].…”
Section: Introductionmentioning
confidence: 99%
“…One can even speculate that the joint evolution of these traits allowed orchids, one of the largest plant families with 27 000 species, to undergo greater diversification than families displaying symbiotic germination or pollinia dispersal alone. Interestingly, pyroloids, a tribe of Ericaceae with small seeds, symbiotic germination (Hashimoto et al ., ) and large seed production (Johansson et al ., ), also tend to transfer pollen clusters by way of insects, that is, in tetrads or even larger aggregates (Takahashi, ). This striking convergence suggests that symbiotic germination and transfer of pollen aggregates sometimes reinforce each other in evolution.…”
mentioning
confidence: 99%